A socio-economic study of an informal sector the case of the street vendors in downtown Bacolod. - Mecabalo, Cherry Belle Sanares
This paper provides a background and basic information on the current social, demographic economic and vending characteristics of the vendors in Downtown Bacolod and their households. Eighty-eight (88) were chosen out of 704 vendors. A one-shot interview was then conducted., the vendors were mostly married females belonging to the 3`-50 years old age bracket. Most of them have reached the high school level of education (7-10 years of schooling) and were also Roman Catholic in religious affiliation. A large percentage of the sample (86.4%) owned the houses though only 19.3% built them on their own lots. A majority (62.5%) built them on government or privately owned lots as squatters. There were also 86.4% who had access to electricity and 66% had access to toilet facilities. The piped water was the main source of drinking water for 54.5% of the sample while only 29.6% had the same source for non-drinking purposes. As to their characteristics, 86% vend daily and 9-12 hours a day vending. Their vending experience were mostly 11-20 years or even more than 20 years (28.4% each). Though some engaged in vending because they had no other alternative (26.1%), most vendors considered it as their main choice of occupation (45.5%). The choice of location was mostly based on its availability (37.5). Most vendors financed their business through their savings (39.8%) while only 3.4% had access to banks. The most common good sold were the food products (45.5%), excluding fruits and fishes. The goods were mostly purchased and sold in cash. The economic conditions of the vendors show an average income of P276.48, twice higher than the legal minimum wage received by the non-agricultural sector of the region (P114). The semi-fixed vendors were better off on the basis of Engel's coefficient while the fixed vendors had the highest savings at P5206.8 per month. The ambulant vendors were the poorest in both categories.